The The Effect of Bingo Game Toward Students Vocabulary Mastery at The Seventh Grade Students of Madrasah Tsanawiyah (MTs) Daar El- Kutub Bayah Lebak Banten in Academic Year 2021/2022 - Nadiya, Ashfa; Rohimajaya, Nur Azmi; Gumelar, Rizdki Elang (Universitas Mathla'ul Anwar Banten, 2022)
This research paper aims to know whether there is a significant effect of Bingo game towards Students’ Vocabulary Mastery at the Seventh Grade of MTS DAAR EL-KUTUB Bayah, Lebak-Banten in Academic Year 2021/2022. The research paper used the quantitative approach and quasi-experimental design. The technique in choosing the sample is cluster random sampling; the researcher used VII A (20 students) as class experimental and VII B (20 students) as class control. In the Collecting data technique, the researcher gives pre-test and post-test. In analyzing the data, the researcher used SPSS 22 statistical computation and used the result of the post-test both class control and experimental to analyze the hypotheses test. The researcher has found the result of Significant two-tailed = 0.000 < α 0.05. Therefore, the researcher concluded that the usage of bingo game has a significant impact on students’ vocabulary mastery in MTs Daar El-Kutub Bayah, Lebak-Banten